Analysis of Earnings Management Practices Using the Modified Jones Model on the Industry Company Index Kompas 100 - Azizah Defi Indriani; Pujiono Pujiono (Universitas Hayam Wuruk Perbanas, 2021)
This study aimed to examine the issue of differences in earnings management patterns in companies listed on the Indonesia Stock Exchange (IDX). Earnings management can occur because company management wants to take advantage of accounting descriptions/policies under the character of the assets, existing in each of these industries. This study used a Modified Jones Model approach in determining earnings management proxies. Besides, it also used analysis of variance (ANOVA) to test whether there were differences in earnings management patterns. The data were consisted of 450 companies from 8 industrial sectors in the Kompas 100 Stock Index during 2015-2019. They were from various industries; essential and chemical industry; consumer goods; services; mining, oil, natural gas; plantation; property and real estate; and banking. The result shows that there are differences in earnings management patterns between industrial sectors. Therefore, company management practices earnings management following the characteristics of each industry. The research also suggests that the next study should analyze the comparison of earnings management with other models to determine the consistency of results.